THE ROLE OF TEACHERS IN INCREASING STUDENT MOTIVATION ON LEARNING INDONESIAN LANGUAGE - Marwanto, Marwanto (Universitas Pendidikan Indonesia, 2020)
This study discusses the role of the teacher in increasing student motivation in learning Indonesian. The teacher is a very important figure in the teaching and learning process as a mediator, facilitator, and leader in the class. Teachers and students must be able to communicate well as the principle of communication between teacher and students so that learning goes well. The focus of this research is how the teacher's role in increasing student motivation towards learning Indonesian in Muhammadiyah Plus Salatiga Elementary School. This study uses a questionnaire or questionnaire technique with a population of 53 teachers and 30 subjects or half of the subjects.